(untitled) (Research, Society and Development, 2022)
The aging process has been characterized as a cause for concern and questioning for humanity, being the target of scientific research since antiquity. Given this context, this research aims to evaluate the self-perception of the elderly assisted in a reference center in western Pará, about aging. This is a descriptive, quantitative and transversal study, by means of the application of the Questionnaire of Self-Perception of Aging (QAPE). The research was conducted with 100 elderly people in the first semester of 2018. The results evidenced that regarding the awareness of aging, 93% of those surveyed, are aware of their age, and consider aging as an opportunity to better appreciate the things of life (92%), despite feeling limited in the daily routine due to the aging process (60%). As far as emotional representation is concerned, for 95% of the elderly, aging is not a reason to make them upset. Therefore, we conclude that the elderly studied have a relative perception of aging according to the thematic axes addressed in each variable. Thus, taking into account that this theme is little explored, we reiterate the need to follow up on this research for a continued and more detailed evaluation of this public, in order to seek means to encourage new studies in this area, aiming at measures that improve the quality of life of these elderly.